Y. Kats, Y. Fadieieva. Irony and means of its realization in english literary discourse (translation aspect) - Y. Kats; Y. Fadieieva (Philological Treatises, 2020)
The notion of "irony" exists in various historical-philosophical and linguistic contexts (from Socrates, Aristotle and to Postmodernism). Each era brought its nuances in its content, but in none of the categories of categories it could not claim a leading role. Therefore, the prospects for its development and study remain open. In modern linguistics, irony is considered as a style-building feature of the text, which can be implemented at different language levels, from one word, to a holistic text in a mandatory contextual environment. The great significance of the context for decoding irony is due to its intellectualism and, consequently, the growth of its weight in contemporary art, the expansion of the means and mechanisms for its implementation in artistic texts. In this context, the analysis of linguistic means of irony in the English artistic discourse becomes significant and relevant.